The Modern Wheelbarrow - Mohammad Noor, Hafsa; Ahmad Said Maulana Tukiran,; Aiman Syauqie Razali,; Ameer Harith Azmee Amar Azwan,; Mohd Najib Janon,; Mahmod Abd Hakim Mohamad, (Multidisciplinary Applied Research and Innovation, 2024)
A wheelbarrow is a small usually single-wheeled vehicle that is used for carrying small loads and is fitted with handles at the rear by which it can be pushed and guided. The wheelbarrow is designed to distribute the weight of the load it is carrying between the wheel and the operator. Wheelbarrows consist of 3 simple machines like lever, wheel and axle, and inclined plane. This research assists farmers performing farm and construction workers that may be at risk of developing a low back musculoskeletal injury. As for prevention, effective interventions to reduce pain are needed. The objective is to fabricate alternative wheelbarrow styles that can reduced the force and work done to carry certain amount of load so can reduce the risk getting low back musculoskeletal injury..While performing different wheelbarrow tasks (pushing, pushing over bumps, and dumping). Moreover, this research has discovered that modern wheelbarrow lessen the time time taken on transferring load from one place to another by 53.8% compared to manual wheelbarrow. This result has been collected through some calculations. Additionally, 20% of the load is reduced with the assist of gear reducer system that is attached at the pulley system.The modern wheelbarrow focuses on reducing the force needed to transfer the material using wheelbarrow and the correct body posture that may match the ergonomic standard such as user’s comfort. The results showed that adding brakes on handles as brake and stopping mechanism can fixate the wheelbarrow’s position, four-wheels concept for stabilizing and the pulley and chain system reducing the force needed for elevation. However, these changes did not significantly affect the projected risk values for low back disorders. Additionally, the cost to make this alternative wheelbarrow might be more expensive than regular wheelbarrows. Therefore, the researcher are trying to make this report to convince people